Investigating circulating expression profile for H19, MEG3, and MIAT long noncoding RNAs with miR-135a and miR-29a in chronic kidney disease and renal hemodialysis patients: interrelations with serum sclerostin - Dahpy, Marwa A.; Khairallah, Marwa K.; Naguib, Rania; Khalil, Mona A.; Seif Eldin, Salwa; Sabet, Marwa A.; Kamel, Amira A. (Frontiers in Molecular Biosciences, 2026)
Background and aimChronic kidney disease (CKD) incorporates a variety of progressive kidney function declines, ranging from mild impairment to end-stage renal disease (ESRD). As a global public health problem, early detection and monitoring remain critical for improving patient outcomes. This study aimed to evaluate the potential diagnostic significance and interrelationships of serum sclerostin, lncRNA H19, lncRNA MEG3, lncRNA MIAT, miR-135a, and miR-29a in patients with CKD and those undergoing hemodialysis.MethodsA total of 150 participants were enrolled in this present case–control study: 50 hemodialysis patients, 50 CKD patients, and 50 healthy controls. Circulating serum sclerostin levels were measured using ELISA. Real-time quantitative PCR (RT-qPCR) was used to measure the circulating levels of lncRNAs (H19, MEG3, and MIAT) and microRNAs (miR-135a and miR-29a). A spectrophotometer was used to determine the levels of calcium, creatinine, urea, and phosphorus in the blood.ResultsBoth the CKD and hemodialysis groups displayed significantly elevated levels of all studied biomarkers compared with controls. However, the highest levels of sclerostin, lncRNAs (H19, MEG3, and MIAT), and microRNAs (miR-135a and miR-29a) were found in the hemodialysis group. LncRNA MIAT, miR-135a, and miR-29a showed high sensitivity and specificity in distinguishing CKD patients from healthy controls. Additionally, H19, MEG3, and miR-29a displayed strong differentiating ability between CKD and hemodialysis patients. All studied biomarkers exhibited strong positive correlations. Predictive modeling identified lncRNAs H19, MEG3, and MIAT as significant predictors of hemodialysis status, while sclerostin, MEG3, and MIAT were the strongest predictors of CKD.ConclusionSerum sclerostin, lncRNAs (H19, MEG3, and MIAT), and microRNAs (miR-135a and miR-29a) are significantly interrelated and may serve as promising non-invasive molecular biomarkers for early detection and monitoring of CKD and hemodialysis patients.